Analyzing Sports Sciences Faculty Students' Attitudes towards Folk Dances Lesson - Meltem ALTUNTUĞ; Alparslan ÜNVEREN; Demir ERNEZ (ümit doğan üstün, 2022)
The present study aimed to analyze the attitudes of sports sciences faculty students towards folk dances lesson according to gender and age. A total of 136 students from Uşak University Sports Sciences Faculty (%57,4 male and %42,6 female) voluntarily participated in the study. "Attitudes towards folk dances lesson scale" developed by Turan (2015) was used as the data gathering tool. The scale was consisted of 13 items anchored with a 5 Likert type scale and 1 factor. The data were analyzed with SPSS 22.0 for Windows using independent samples t test and one way Anova. According to analyzed results, there was a significant difference in the attitude towards folk dances lesson according to gender, on the other hand there was no significant difference according to age. As a result, present paper showed that female sports sciences faculty students had a more positive attitude towards folk dances lesson than males.